Relations between the use of performance indicators and the role of individual companies in supply chain coordination process - Chaves, Renata Porto (Management Control Review, 2023)
This paper aims to investigate the relations between the use of performance indicators and the role of individual companies within supply chain coordination process. A survey among 36 individual agribusiness companies was undertaken taking the role of each company in the coordination process of its supply chain into consideration. Senior managers were asked to declare the role of each company in the coordination process of its supply chain as well as to indicate which performance indicators they used through a questionnaire which presented a list composed by 49 performance indicators divided into the four traditional perspectives. Fisher's exact test and a logit model were used to analyze the relations between the usage of performance indicators and the role played in supply chain coordination process. The statistically significant results from Fisher's exact test were relating to inventory, operational costs, operational cycle, information and integration of materials, and risk management. The results from the logit model point out that inventory, and operational costs presented significant predictability levels regarding to the identification of individual supply chain participants, while operational cycle, information and integration of materials, and risk management presented significant predictability levels relating to individual supply chain coordinators. The research carried out in this paper is based on responses provided by senior managers regarding managerial practices and the sample size is limited. However, the results presents a new perspective about the relevance of the role of individual companies within the coordination process of supply chain regarding to performance indicators from which further research may be conducted. The implications relating to management control arising from the findings suggests that metrics selection criteria within in the context of supply chain can be based on both individual motivations and objectives.